2011
DOI: 10.1038/bjc.2011.375
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of irinotecan and gefitinib in patients with gefitinib treatment failure for non-small cell lung cancer

Abstract: Background:Currently, no effective treatments exist for non-small cell lung cancer (NSCLC) after failure of gefitinib therapy. Pre-clinical studies have demonstrated that gefitinib-resistant NSCLC cells are more sensitive to irinotecan than parental cells, and that combined administration of irinotecan and gefitinib has a synergistic additive effect. We conducted a phase I study to evaluate the combination of irinotecan and gefitinib as a therapeutic option for NSCLC patients with progressive disease (PD) afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Therefore, clinical studies of irinotecan plus other agents aimed at improving its safety and efficacy were paid much attention. It was reported that irinotecan in combination with tyrosine kinase inhibitors(TKIs) such as telatinib and sorafenib caused apparent anti-tumor activity in patients with solid tumors and such strategies was tolerated [ 34 , 35 ] which indicated that tyrosine kinase inhibitors may synergize with irinotecan to suppress HCC. Thus, to identify the candidate TKI(s) which could improve the safety and efficacy of irinotecan, we performed an in-vitro screening of a TKI library using a SRB assay.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clinical studies of irinotecan plus other agents aimed at improving its safety and efficacy were paid much attention. It was reported that irinotecan in combination with tyrosine kinase inhibitors(TKIs) such as telatinib and sorafenib caused apparent anti-tumor activity in patients with solid tumors and such strategies was tolerated [ 34 , 35 ] which indicated that tyrosine kinase inhibitors may synergize with irinotecan to suppress HCC. Thus, to identify the candidate TKI(s) which could improve the safety and efficacy of irinotecan, we performed an in-vitro screening of a TKI library using a SRB assay.…”
Section: Discussionmentioning
confidence: 99%
“…A similar strategy was used previously for breast cancer, and is the basis for combined targeted therapy. A study by Nishio et al showed that the epidermal growth factor receptor (EGFR) inhibitor, gefitinib, suppressed serum androgen levels; moreover, gefitinib responders had significantly lower androgen levels than non-responders in female NSCLC patients ( 70 72 ). Kerr et al used laser capture microdissection of tumor specimens to analyze NSCLC gene expression, showing that both ERα and ERβ mRNA transcripts are expressed at higher levels in NSCLC cells compared with normal lung ( 63 ).…”
Section: Literature Analysismentioning
confidence: 99%
“…Apoptotic cell death induced by gefitinib is accompanied by G0/G1 cell cycle arrest with down-regulation of CDKs/cyclins [13] and anti-apoptotic proteins [12]. Moreover, gefitinib alone or in combination with other chemotherapy shows clinically meaningful antitumor activity in patients with advanced lung cancer [14-16]. However, the therapeutic efficacy of gefitinib increases noticeably in patients with lung cancer who have somatic mutations in the EGFR TK domain such as deletions in exon 19 or a point mutation (L858R) in exon 21 [17, 18].…”
Section: Introductionmentioning
confidence: 99%